Antibacterial mechanism of hyper-branched poly-L-lysine against methicillin-resistant Staphylococcus aureus and its synergistic and antagonistic interactions with conventional antibiotics - Wang, Yaoqin; Wu, Qiaoli; Mao, Guofeng; Rao, Lulin; Liang, Meichun; Sun, He (Frontiers in Microbiology, 2025)
The global proliferation of multidrug-resistant pathogens, particularly methicillin-resistant Staphylococcus aureus (MRSA), constitutes a severe threat to public health, rendering many conventional antibiotics obsolete. In the post-antibiotic era, where the pace of bacterial resistance evolution far exceeds that of new drug discovery, novel therapeutic strategies are urgently required. This study investigates the antibacterial potential of hyper-branched poly-L-lysine (HBPL), a synthetic antimicrobial polymer, against MRSA. We elucidate a multi-modal, physically disruptive mechanism of action initiated by electrostatic binding to the bacterial envelope, followed by rapid membrane permeabilization and cellular collapse, as visualized by electron and confocal microscopy. HBPL demonstrated potent, concentration-dependent bactericidal activity against clinical and standard MRSA strains, with a minimum inhibitory concentration (MIC) of 0.5 mg/mL and a minimum bactericidal concentration (MBC) of 1.0 mg/mL. Furthermore, HBPL inhibited biofilm formation by three MRSA strains (87, 73, and 81%) at a concentration of 1.0 mg/mL, which is a great advantage against the persistent and recalcitrant nature of biofilm-associated infections. Combination therapy studies using checkerboard assays revealed mechanistically dependent interactions. A synergistic effect [fractional inhibitory concentration index (FICI) ≤0.5] was observed with levofloxacin, attributed to HBPL-mediated membrane permeabilization enhancing intracellular drug access. Conversely, antagonism (FICI > 4) was noted with daptomycin, likely due to competitive binding at the bacterial membrane. These findings underscore the importance of rational drug pairing. While prolonged exposure induced stable, low-level resistance in MRSA, this was associated with adaptive cell envelope remodeling rather than target-site mutation. Collectively, this research establishes HBPL as a promising membrane-active agent and adjuvant therapy, capable of not only direct bactericidal action but also of restoring the efficacy of existing antibiotics against formidable pathogens like MRSA.